Gravimetric geoid determination in Metro Manila by using terrestrial and satellite-derived data - Meneses, Serafin Farley M. (2009)
Geoid models, normally used as vertical reference frames, find many applications in a plane and geodetic engineering surveys. In fact, one of the reasons that some geoid models were developed was to respond to global positioning system (GPS) users who demand accurate goid models. The utmost aim of this research is the utilization of remotely-sensed data for gravimetric geoid determination in Metro Manila. Satellite-derived data were used to derive short and long wavelength gravity information. These two components, along with the medium wavelength gravity information, are important elements of the solution of the geodetic boundary value problem/Stokes? integral for the determination of geoid undulations. Also, it shown in this research that remotely-sensed data serve as invaluable sources of supplemental information here in the Philippines since there is limited or lacking publicly available gravity-related information here. However, it is not the intention of this research to provide geophysical interpretations of the results. As such, interpretations lean towards geodetic engineering or towards the geometric characteristics of the results. The final geoid model of Metro Manila was computed by adding the GGM-derived geoid, geoidal undulations derived by using Faye anomalies and Stokes' integral, and the indirect effect. Due to the relative magnitudes of each of the components, it is obvious that the GGM-derived geoidal undulations would dominate the values of the final geoidal undulations. As expected, statistics of the final geoidal undulations is similar to that of the GGM-derived geoidal undulation: maximum values is about 45.70 m, minimum is 44.34 m, mean is 45.07 m, and standard deviation is only 0.31 m. In order to fit the derived equipotential surface to existing GPS/leveling net within the study area, a four parameter Helmert transformation was done. As expected the ?fitted? geoid gives the best residuals with respect to Metro Manila GPS/leveling stations. It is recommended that more accurate and precise terrestrial gravity measurements suitable for geoid determination be made. Other sources of information may also be used in future geoid researches like bathymetry and altimetry data. More detailed topography information may also be investigated (i.e. improvement of the estimate of the crustal density, creation of a higher resolution DEM, etc.) In addition, other methods of gravimetric geoid determination solution should also be tested so that an optimal geoid model for Metro Manila be achieved.
"May 2009."
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman.
Keywords: Quantum gravity